P2_1 James’ Giant Peach Transport across the Atlantic - Watkinson, Emily Jane; Walach, Maria-Theresia; Staab, Daniel; Rogerson, Zach (Physics Special Topics, 2012)
In Roald Dahl's children's classic James and the Giant Peacha magically enlarged fruit travels across the Atlantic Ocean, partly floated on the water and partly airlifted by a flock of seagulls. Through examining the buoyancy and modelling the seagulls as aerofoils it has been found that although the initial part of the journey is possible, given a sufficiently hollow peach, James would have to tether approximately two and a half million Common Gulls, rather than the 501 as described in the book.